1971
DOI: 10.1139/o71-012
|View full text |Cite
|
Sign up to set email alerts
|

The Isolation and Identification of Androstenediol Sulfate from Spermatic Vein Blood and Testes of the Boar

Abstract: RAESIDE, J. I., AND HOWELES, G . A. The isogation and identification of androstenedioi sulfate from spermatic vein blood and testes of the boar. Can. J. Biochern. 49, 80-84 (1971).A method is described for the extraction and purification of steroid sulfates from testicdar tissues and blood of the boar. Androsteraediol sulfate (3b91'9S-dihydroxy-5-andPo9tene 3-sulfate) was isolated from extracts of both spermatic vein blood and boar testis. Final identification was achieved by infrared spectroscopy, as the amms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

1973
1973
2005
2005

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…Studies on the production of testicular androgens in the dog (Oh & Tamaoki, 1973) have shown that testosterone can be synthesized from 3/?-hydroxy-5-ene-C19 steroids without the intermediate formation of androstenedione. The significant amounts of dehydroepiandrosterone sulphate (Baulieu et al, 1967) and 5-androstenediol sulphate (Raeside & Howells, 1971) which were found in the testis and spermatic vein blood of the boar suggests that the 5-ene pathway to testosterone may be important in this species.…”
Section: Introductionmentioning
confidence: 95%
“…Studies on the production of testicular androgens in the dog (Oh & Tamaoki, 1973) have shown that testosterone can be synthesized from 3/?-hydroxy-5-ene-C19 steroids without the intermediate formation of androstenedione. The significant amounts of dehydroepiandrosterone sulphate (Baulieu et al, 1967) and 5-androstenediol sulphate (Raeside & Howells, 1971) which were found in the testis and spermatic vein blood of the boar suggests that the 5-ene pathway to testosterone may be important in this species.…”
Section: Introductionmentioning
confidence: 95%
“…Plasma concentrations of many steroid sulphates are substantially higher than that of their unconjugated forms [14,15]. In fact, dehydroepiandrosterone (DHEA) has been reported to be present primarily as a sulphoconjugate in porcine plasma, such that only 10-15% is in the nonconjugated form [16].…”
Section: Introductionmentioning
confidence: 99%
“…The testis of the male pig produces, in addition to testosterone, large quantities of other C,9 steroids (Baulieu, Fabre-Jung & Huis in't Veld, 1967;Raeside & Howells, 1971; Ruokonen & Vihko, 1974;Segal & Raeside, 1975;Booth, 1975). Some of these C19 steroids, notably dehydroepiandrosterone (DHA) and 5-androstenediol may be important precursors of testosterone in the pig testis, as they are in the testis of dogs (Yamaji, Motohashi, Tanioka & Ibayashi, 1968;Oh & Tamaoki, 1973) and man (Vihko & Ruokonen, 1975).…”
Section: Introductionmentioning
confidence: 99%